New donor-acceptor-donor type of organic semiconductors based on the regioisomers of diketopyrrolopyrroles: A DFT study. (December 2020) - Gogoi, Gautomi; Bhattacharya, Labanya; Rahman, Shohidur; Sarma, Neelotpal Sen; Sahu, Sridhar; Rajbongshi, Basanta Kumar; Sharma, Sagar
Abstract: The present work describes computational studies on structural, electronic, charge transport and photovoltaic properties of donor-acceptor-donor (D-A-D) type of compounds based on two regioisomers of diketopyrrolopyrrole. Diketopyrrolo[3, 4- c ]pyrrole (DPP1), a well known electron acceptor moiety and its regioisomer diketopyrrolo[3, 2- b ]pyrrole (DPP2) are coupled with various electron donor groups containing fused ring system to obtain model compounds of D-A-D type of architecture. The donor groups include meta-benzodithiophene, ortho-benzodithiophene, carbazole, dithienopyrrole, dithienosilole and dithienothiophene. An analysis of their properties reveal that these compounds possess unique characteristics and advantages over each other. Density functional theory (DFT) calculations show that the DPP2-based compounds exhibit lower hole reorganization energy (λh ) than the corresponding DPP1-based compounds, while the DPP1-based compounds have lower electron reorganization energy (λe ) than the corresponding DPP2-based compounds, which is in line with the observed ionizational potential (IP) and electron affinity (EA) values. The calculated open circuit voltage ( Voc ) and the fill factor (FF) values of the DPP2-based compounds as donors with fullerene-like PC61 BM as an acceptor are higher than the DPP1-based compounds as donors. Charge density difference (CDD) calculation shows DPP2 based compounds exhibit better intramolecular charge transfer (ICT) properties as compared to their DPP1 counterpart. The weaker electron-hole coherence may lead to easy exciton dissociation in case of DPP1-based compounds at donor/acceptor interface, which is also supported by their comparatively lower exciton binding energy as compared to DPP2 counterparts.